Genomic signatures of different adaptations to environmental stimuli between wild and cultivated Vitis vinifera L. Issue 1 (1st July 2018) - Marrano, Annarita; Micheletti, Diego; Lorenzi, Silvia; Neale, David; Grando, M Stella
Abstract: The application of population genetic methods in combination with gene mapping strategies can help to identify genes and mutations selected during the evolution from wild plants to crops and to explore the considerable genetic variation still maintained in natural populations. We genotyped a grapevine germplasm collection of 44 wild ( Vitis vinifera subsp. sylvestris ) and 48 cultivated ( V. vinifera subsp. sativa ) accessions at 54 K single-nucleotide polymorphisms (SNPs) to perform a whole-genome comparison of the main population genetic statistics. The analysis of Wright Fixation Index ( F ST ) along the whole genome allowed us to identify several putative "signatures of selection" spanning over two thousand SNPs significantly differentiated between sativa and sylvestris . Many of these genomic regions included genes involved in the adaptation to environmental changes. An overall reduction of nucleotide diversity was observed across the whole genome within sylvestris, supporting a small effective population size of the wild grapevine. Tajima's D resulted positive in both wild and cultivated subgroups, which may indicate an ongoing balancing selection. Association mapping for six domestication-related traits was performed in combination with population genetics, providing further evidence of different perception and response to environmental stresses between sativa and sylvestris . Grapes: Wild and cultivated grapevines adapted to different stresses: Wild and domesticated grapevine populations display genomic differences that likely arose as a result of evolutionary responses to different environmental pressures. Annarita Marrano of the Edmund Mach Foundation in San Michele All'adige, Italy, and colleagues characterized the genetic diversity found in 44 wild and 48 cultivated accessions of the Eurasian wine grape, Vitis vinifera . They analyzed 54, 000 single DNA letters spread across the genome and found evidence that natural wild grapevine populations are on the decline. They also identified several genomic regions related to stress responses that evolved differently in grapes bred to live in vineyards and their wild relatives. The findings suggest the need to conserve wild grapevines, which may harbor genes encoding resilience factors that could aid in the development of hardier wine-producing crops in the future.